Insights into Normal Myelopoiesis - Dennis G Osmond (Canadian Journal of Infectious Diseases)
Recent in vivo studies provide working models of cell production and cell loss in myelopoiesis, as exemplified by B lymphopoiesis in mouse bone marrow. The process is susceptible to both local and systemic regulatory influences and shows a complex tissue organization. Early precursor cells tend to be located in microenvironments towards the edge of the bone marrow near the surrounding bone. Differentiating precursor cells adhere to local stromal reticular cells, representing a cellular interaction which is essential for further B cell development. Many defective or unacceptable B precursor cells are selected out and deleted by resident bone marrow macrophages. Maturing B cells congregate in segments of venous sinusoids before being released into the blood circulation . Rapid progress is being made in elucidating the nature of the cytokines, extracellular matrix and cell adhesion molecules involved in normal regulation and perturbations of primary B lymphopoiesis in vivo.